2020
DOI: 10.18502/jovr.v15i1.5960
|View full text |Cite
|
Sign up to set email alerts
|

Torpedo Maculopathy

Abstract: This is a Photo Essay and does not have an abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We read with great interest the recent case series by Venkatesh and colleagues about the spectrum and features of Torpedo lesions described in nine subjects. [1] As far as we are aware, the Journal of Ophthalmic and Vision Research has recently published another report on the same topic, [2] and we have encountered such rare cases in our daily practice at Labbafinejad Medical Center as one of the main tertiary centers for retinal diseases. Herein, we would like to draw the kind attention of readers toward some pathophysiologic issues about the origin of Torpedo lesions.…”
Section: Dear Editormentioning
confidence: 98%
See 2 more Smart Citations
“…We read with great interest the recent case series by Venkatesh and colleagues about the spectrum and features of Torpedo lesions described in nine subjects. [1] As far as we are aware, the Journal of Ophthalmic and Vision Research has recently published another report on the same topic, [2] and we have encountered such rare cases in our daily practice at Labbafinejad Medical Center as one of the main tertiary centers for retinal diseases. Herein, we would like to draw the kind attention of readers toward some pathophysiologic issues about the origin of Torpedo lesions.…”
Section: Dear Editormentioning
confidence: 98%
“…As well as the known term "Torpedo maculopathy (TM)", other nomenclatures, are sparsely used as paramacular albinotic spot syndrome, congenital hypomelanotic freckle, and atypical macular coloboma. [1][2][3][4] The embryonal origin of these congenital lesions is believed to be rooted in maldevelopment of RPE and disturbances of choroidal vasculature. Furthermore, as discussed in a very recent systematic review, subtypes II and III of Torpedo lesions have been suggested to be classified as choroidal cavitary disorders.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…On fundus autofluorescence, TM lesions exhibit hypo-autofluorescence with a surrounding cuff of hyper-autofluorescence [11]. The hypo-autofluorescence exhibited by the lesion corresponds to atrophic RPE while the cuff of hyper-autofluorescence indicates the accumulation of lipofuscin inside retinal pigment epithelial cells [9].…”
Section: Diagnostic Imagingmentioning
confidence: 99%